Unilateral Internuclear Ophthalmoplegia From Infarction Origin: Small Lesion Big Trouble - Shavira Kartika Dewi Safitri; M. Nurdin Zuhri (Universitas Airlangga, 2026)
Introduction: Internuclear ophthalmoplegia (INO) is an ocular movement disorder caused by a lesion of the medial longitudinal fasciculus (MLF). Approximately one-third of INO cases are due to infarctions, typically unilateral and affecting older adults. This case report presents a patient with unilateral INO and a one-month follow-up after therapy. Case Presentation: A 55-year-old woman presented with double vision, particularly on the left, which had persisted for one month. She also reported blurry vision in both eyes, especially in the right eye, and occasional headaches. The right eye best corrected visual acuity (BCVA) was 5/7.5 cc S -0.75; became 5/6 with no improvement with pinhole. The left eye BCVA was 5/6 cc S -0.5 C -0.5 A 50, became 5/5. The right eye ocular motility was -4 when the eye gazed in the nasal direction. Slowed adducting saccadic velocity was observed in the right eye, with left-eye abducting nystagmus. The brain magnetic resonance imaging (MRI) revealed a small infarct in the right MLF. The patient had a history of uncontrolled hypertension and type 2 diabetes mellitus. She was diagnosed with unilateral INO and treated with mecobalamin, metformin, vitamin B complex, amlodipine, candesartan, and atorvastatin. At one-month follow-up, ocular motility had improved to -2 in the right eye on nasally directed gaze, and the patient reported a reduction in double vision. Conclusions: Small infarcts in the right MLF can cause significant diplopia. Isolated unilateral INO may be the sole manifestation of ischemic stroke and generally has a good prognosis with appropriate management.